2011
DOI: 10.1038/bjc.2011.495
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of dual PI3K-mTOR inhibitors and histone deacetylase inhibitors in head and neck squamous cell carcinoma

Abstract: Background:We examine the potential value of a series of clinically relevant PI3K-mTOR inhibitors alone, or in combination with histone deacetylase inhibitors, in a model of head and neck squamous cell carcinoma (HNSCC).Methods:Head and neck squamous cell carcinoma cell lines, human keratinocyte and HNSCC xenograft models were treated with histone deacetylase inhibitors (HDACIs) and new generation PI3K and dual PI3K-mTOR inhibitors either alone or in combination. Cell and tumour tissue viability and proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 41 publications
4
54
1
Order By: Relevance
“…An examination of the potential value of PI3K/mTOR inhibitors alone or in combination with histone deacetylase (HDAC) inhibitors in an in vitro model of SCCHN revealed marked enhancement of HDAC inhibitor-induced cytotoxicity by PI3K, AKT, and dual PI3K-mTOR inhibitors [49]. This effect correlated with AKT inhibition and was attenuated by expression of constitutively active AKT.…”
Section: Dual Pi3k/mtor Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…An examination of the potential value of PI3K/mTOR inhibitors alone or in combination with histone deacetylase (HDAC) inhibitors in an in vitro model of SCCHN revealed marked enhancement of HDAC inhibitor-induced cytotoxicity by PI3K, AKT, and dual PI3K-mTOR inhibitors [49]. This effect correlated with AKT inhibition and was attenuated by expression of constitutively active AKT.…”
Section: Dual Pi3k/mtor Inhibitionmentioning
confidence: 99%
“…Buparlisib demonstrates synergistic activity with cytotoxic and targeted agents [46,47], and enhances sensitivity to these drugs in resistant cancer models [48]. Buparlisib has also been shown to enhance the in vitro cytotoxicity of histone deacetylase inhibitors in SCCHN cancer cells and to inhibit tumor growth in xenograft models of SCCHN [49]. PX-866 is another agent that has demonstrated antitumor efficacy in SCCHN models with PIK3CA alterations [45].…”
Section: Pan-pi3k Inhibitionmentioning
confidence: 99%
“…HDAC inhibitors may therefore also be useful for the treatment of those HNSCC that show overexpression of Ano1 and concomitant activation of cyclin D1 [23]. In fact, HDAC inhibitors have already entered preclinical evaluation [42,43]. In recent experiments, we found that pronounced expression of Ano1 in the HNSCC cell line BHY was largely inhibited by treatment with the HDCA inhibitors valproic acid or butyric acid, along with inhibition of cell survival and Ano1-dependent whole cell currents ( figure 3a-f ) rstb.royalsocietypublishing.org Phil.…”
Section: Regulation Of Expression Of Ano1 By Histone Deacetylase and mentioning
confidence: 99%
“…BGT26 was provided by Novartis, and stocks of BGT226 were prepared as described (16). ZVAD-fmk was added 30 minutes before other treatments.…”
Section: Chemicals and Viability Assaysmentioning
confidence: 99%